(untitled) (Intent Research Scientific Journal, 2023)
In this article, a new type of closed bed ditch was installed and experiments were conducted in the conditions of medium and strong saline soils of Jizzakh region. According to the results of the experiment, the results of the scientific research on cotton growth, development and yield of the amount of water used in the periods of salt washing and cotton irrigation in the variants with a closed ditch and a new type of closed ditch are described.